Defective porous carbon material, preparation method and application thereof, and supercapacitor

By designing defects on porous carbon materials, controlling their surface charge distribution and electron transfer rate, the problem of limited working voltage of supercapacitor electrode materials is solved, and the working potential range and energy density of the electrode materials are expanded, which is suitable for building high Performance supercapacitor.

CN119252672APending Publication Date: 2025-01-03ANHUI GLANCO NEW MATERIAL TECH CO LTD +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411317871.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-20
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The existing supercapacitor electrode materials are limited in operating voltage, making it difficult to broaden the window of stable operating potential, resulting in insufficient energy density and stability.

Method used

By designing defects on porous carbon materials, the surface charge distribution and electron transfer rate are regulated, and additional electron adsorption sites are formed to expand the operating voltage range of the electrode.

Benefits of technology

It has achieved the expansion of the working potential range of the supercapacitor, improved its energy density and stability, and is suitable for building energy storage devices with wide potential range and high specific capacity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119252672A_ABST
    Figure CN119252672A_ABST
Patent Text Reader

Abstract

The invention discloses a defect type porous carbon material, a preparation method and application thereof, and a supercapacitor, and relates to the technical field of supercapacitor electrode materials, the defect type porous carbon material is subjected to defect design, so that electronegativity regulation and control of the surface of an electrode can be realized, and the working potential range of the electrode is expanded; the method for expanding the stable working potential range of the porous carbon material provided by the invention has the advantages of flexibility, adjustability, simple process and easiness in implementation, and has important significance for constructing a supercapacitor energy storage device with a wide potential range, high specific capacity and excellent stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of supercapacitor electrode materials, and in particular to a defective porous carbon material, a preparation method and application thereof, and a supercapacitor. Background Art

[0002] With the rapid development of energy storage technology, supercapacitors have gradually attracted attention for their higher energy density and stability and fast charge and discharge characteristics that are superior to battery energy storage technology. Among them, the wide voltage of organic supercapacitors or the high specific capacitance of aqueous supercapacitors are two common means to achieve excellent performance of supercapacitors. However, although organic supercapacitors rely on the wide potential range obtained by organic electrolytes to show excellent stability during charge and discharge, it is difficult to continue to improve the energy density of the device due to the characteristics of the electrode material itself storing energy in physical form. In addition, in aqueous supercapacitors, although the energy density has been significantly improved by compounding substances that can undergo pseudocapacitive reactions in conductive active materials, it is limited by the hydrolysis reaction of the electrode when the potential exceeds 1.23V. In actual use, more devices need to be connected in series to achieve the required working voltage, which not only increases the ineffective weight, but also reduces the energy density of the device. In summary, exploring a method to broaden the working voltage range of carbon electrode materials is particularly important for designing supercapacitors with both a wide potential range and high energy density.

[0003] Generally speaking, when the electrochemical reaction rates of the positive and negative carbon electrode materials are consistent, the working voltage of the supercapacitor is equal to the sum of the absolute values ​​of the working voltages of the positive electrode material and the negative electrode material. Therefore, assembling positive and negative electrodes with different energy storage characteristics into an asymmetric supercapacitor can obtain a significantly improved working potential window. In the assembly process of an asymmetric supercapacitor, the good matching relationship between the positive and negative electrodes depends not only on the specific capacity of the electrode material itself, but also on the initial potential P0 of the electrode material. By changing the P 0V When the position is set at the ideal position of the positive and negative electrode materials, the electrochemical reaction capacity of the electrode is enhanced, and the assembled asymmetric supercapacitor device can also obtain the widest potential range. 0V It is the key to broadening the stable operating voltage range of carbon electrode materials.

[0004] Defect engineering of carbon electrode materials can regulate their electronegativity, thereby changing the P 0V By forming additional electron adsorption sites on the surface or inside the porous carbon electrode material, not only the active site density and electron transfer rate on the electrode surface can be changed, but also the surface energy and charge distribution on the electrode surface can be adjusted, causing the energy storage reaction process of the carbon electrode material to change, and ultimately achieving the purpose of regulating the stable working potential of the porous carbon electrode material. Summary of the invention

[0005] The technical problem to be solved by the present invention is to provide a method for preparing defective porous carbon materials, by designing defects in the porous carbon materials to change the surface charge distribution of the electrode prepared therefrom, so that the open circuit voltage of the electrode reaches an ideal state, thereby achieving the purpose of widening the stable working potential window.

[0006] The technical problem to be solved by the present invention is achieved by adopting the following technical solutions:

[0007] The first object of the present invention is to provide a method for preparing a defective porous carbon material, comprising the following steps:

[0008] (1) preparing a carbon precursor solution and uniformly coating the solution on a flexible substrate, and drying the solution to obtain a carbon precursor film;

[0009] (2) pretreating the carbon precursor film;

[0010] (3) The pretreated film is subjected to defect design and carbonization treatment to obtain a defective porous carbon material.

[0011] The second object of the present invention is to provide a defective porous carbon material prepared by the aforementioned preparation method.

[0012] The third object of the present invention is to provide application of the defective porous carbon material as an electrode material.

[0013] The fourth object of the present invention is to provide an asymmetric supercapacitor, using the defective porous carbon material as an electrode material. Specifically, the defective porous carbon material with a stable working potential range of positive values ​​is used as the positive electrode, and the defective porous carbon material with a stable working potential range of negative values ​​is used as the negative electrode.

[0014] The beneficial effects of the present invention are:

[0015] (1) The present invention can achieve the regulation of the electronegativity of the electrode surface by defect design of the porous carbon material, so that the working potential range of the electrode is expanded.

[0016] (2) The method for expanding the stable working potential range of porous carbon materials provided by the present invention has the advantages of flexible adjustability, simple process and easy implementation, which is of great significance for constructing supercapacitor energy storage devices with a wide potential range, high specific capacity and excellent stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 This is a surface SEM image of the porous carbon material containing sulfur at defect sites prepared in Example 1;

[0018] Figure 2This is a surface element distribution diagram of the porous carbon material containing sulfur at defect sites prepared in Example 1;

[0019] Figure 3 The P0 position change of the three-electrode test system assembled by using the porous carbon material containing sulfur at the defect site prepared by laser scanning the phenolic resin film 1 to 5 times in step (5) of Example 1 as the working electrode;

[0020] Figure 4 The CV graph of a three-electrode test system assembled using the porous carbon material containing sulfur at defect sites prepared in Example 1 as a working electrode at 0 to 1.2 V;

[0021] Figure 5 The GCD diagram of the three-electrode test system assembled using the porous carbon material containing nitrogen at defect sites prepared in Example 2 as the working electrode at 0-1.2V;

[0022] Figure 6 This is a surface SEM image of the iron oxide composite porous carbon material prepared in Example 3;

[0023] Figure 7 The CV graph of the three-electrode test system assembled using the iron oxide composite porous carbon material prepared in Example 3 as the working electrode at -1.2 to 0 V;

[0024] Figure 8 The GCD diagram of the three-electrode test system assembled using the iron oxide composite porous carbon material prepared in Example 3 as the working electrode at -1.2 to 0 V;

[0025] Fig. 9 This is a surface SEM image of the porous carbon material containing sulfur at defect sites prepared in Example 4;

[0026] Fig.10 This is a cross-sectional SEM image of the phenolic resin film after preforming in Example 5;

[0027] Fig.11 This is a surface SEM image of the porous carbon material containing sulfur at defect sites prepared in Example 6;

[0028] Fig.12 The CV curve of a three-electrode test system assembled using the porous carbon material containing sulfur at defect sites prepared in Comparative Example 1 as the working electrode;

[0029] Fig.13 This is the surface element distribution diagram of the porous carbon material prepared in Comparative Example 2;

[0030] Fig.14 It is the CV curve of the three-electrode test system assembled using the porous carbon material prepared in Comparative Example 2 as the working electrode. DETAILED DESCRIPTION

[0031] In order to make the technical means, creative features, objectives and effects achieved by the present invention easy to understand, the present invention is further described below in conjunction with specific embodiments and diagrams.

[0032] The present invention provides a method for preparing a defective porous carbon material, comprising the following steps:

[0033] (1) preparing a carbon precursor solution and uniformly coating the solution on a flexible substrate, and drying the solution to obtain a carbon precursor film;

[0034] (2) pretreating the carbon precursor film;

[0035] (3) The pretreated film is subjected to defect design and carbonization treatment to obtain a defective porous carbon material.

[0036] Furthermore, the carbon precursor is one or more of polymers containing benzene rings such as phenolic resin, epoxy resin, polyimide, polyamic acid, and polyether sulfone.

[0037] A thermally stable carbon precursor is selected as a carbon source and mixed with an easily removable organic solvent to form a solution. Specifically, the organic solvent is an organic solvent such as ethanol, methanol, propanol, etc. with a mass fraction of 20 to 100%.

[0038] Furthermore, the coating method includes but is not limited to one or more of a self-leveling method, a wire rod coating method, a four-sided scraper coating method, a mold coating method, and a coater coating method, and the coating thickness is 10 to 2000 μm.

[0039] Furthermore, the flexible substrate includes but is not limited to one or more of PET film, copper foil, carbon-coated copper foil, copper mesh, aluminum foil, carbon-coated aluminum foil, aluminum mesh, titanium foil, stainless steel foil, nickel foil, foam nickel, and carbon paper, with a thickness of 5 to 200 μm.

[0040] Furthermore, the drying method includes but is not limited to one or more of room temperature drying, oven drying, and vacuum drying. The drying temperature is 30 to 300° C. and the drying time is 1 to 24 hours.

[0041] Furthermore, the pretreatment includes but is not limited to one or more of high-energy beam etching scanning, low-temperature heating treatment, and rapid flash technology treatment.

[0042] The purpose of pretreatment is to form partially disordered carbon chains and pre-shape the carbon precursor film.

[0043] Furthermore, the carbonization treatment includes but is not limited to one or more of high temperature carbonization, high energy beam etching scanning, flash Joule heat treatment, and hydrothermal reaction, and the treatment temperature is 300 to 3000°C.

[0044] Furthermore, the defect design methods include but are not limited to one or more of the following: compounding of non-metallic atoms with edge carbon atoms, removing carbon atoms on the carbon layer to form nanopores, and embedding metal oxides or hydroxides in macroscopic defects to obtain a continuous structure.

[0045] The present invention provides a defective porous carbon material prepared by the aforementioned preparation method.

[0046] The invention provides application of the defective porous carbon material as an electrode material.

[0047] The present invention provides an asymmetric supercapacitor, using the defective porous carbon material as an electrode material. Specifically, the defective porous carbon material with a stable working potential range of positive values ​​is used as the positive electrode, and the defective porous carbon material with a stable working potential range of negative values ​​is used as the negative electrode.

[0048] The technical solution of the present invention is described in detail below through specific embodiments.

[0049] Example 1

[0050] (1) Weigh 5 g of phenolic resin powder and mix it with 15 mL of anhydrous ethanol, and stir it with a magnetic stirrer at a speed of 800 r / min for 5 h to obtain a phenolic resin solution.

[0051] (2) The phenolic resin solution prepared above was coated on a nickel foam with a thickness of 50 μm by wire rod coating, and then placed in a 50° C. oven for drying for 5 h. After being completely dried, the solution was taken out from the oven to obtain a phenolic resin film.

[0052] (3) The phenolic resin film prepared above was exposed to a low-energy CO2 laser beam for pretreatment to form a partially disordered carbon chain, which played a pre-setting role on the phenolic resin film. The laser power was 2.5 W, the laser scanning speed was 50 mm / s, and the laser line spacing was 0.1 mm.

[0053] (4) The phenolic resin film pretreated with low-energy laser is placed in a 1 M sodium sulfide solution and ultrasonically treated for 30 minutes, so that the sodium sulfide solution adheres to the surface of the pre-shaped phenolic resin film.

[0054] (5) exposing the phenolic resin film treated in step (4) to irradiation of a CO2 laser beam again, with the laser parameters being consistent with those in step (3), and repeating the process 5 times to completely carbonize the phenolic resin film, and then washing the film with deionized water 3 times to obtain a porous carbon material containing sulfur at defect sites.

[0055] The porous carbon material containing sulfur at the defect sites prepared in Example 1 was used as a working electrode, a metal platinum sheet was used as a working electrode, a saturated calomel electrode was used as a reference electrode, and a lithium chloride solution with a concentration of 1 M was used as an electrolyte to assemble a three-electrode test system. Cyclic voltammetry (CV), constant current charge and discharge (GCD), and open circuit voltage (P0) tests were performed on an electrochemical workstation. The voltage scan rate of the CV test was 20 to 100 mV / s, and the current density of the GCD test was 1 to 9 mA / cm 2 .

[0056] Figure 1 This is a surface SEM image of the porous carbon material containing sulfur at defect sites prepared in Example 1. Figure 1 It can be seen that the porous carbon material containing sulfur at defect sites prepared in Example 1 has a typical three-dimensional porous and lamellar network structure, which can provide abundant active sites for electrochemical reactions.

[0057] Figure 2 This is the surface element distribution diagram of the porous carbon material containing sulfur at defect sites prepared in Example 1. Figure 2 It can be seen that the surface of the porous carbon material containing sulfur at defect sites prepared in Example 1 has abundant S defect sites.

[0058] Figure 3 The P0 position change of the three-electrode test system assembled using the porous carbon material containing sulfur at the defect site prepared in Example 1 as the working electrode. Figure 3 It can be seen that as the number of laser scans on the film in step (5) increases, using the porous carbon material containing sulfur at defect sites prepared in Example 1 as the working electrode can increase the initial voltage P0 position from 0.08V to 0.36V.

[0059] Figure 4 The CV graph of the three-electrode test system assembled using the porous carbon material containing sulfur at defect sites prepared in Example 1 as the working electrode at 0 to 1.2 V. Figure 4 It can be seen that compared with the traditional porous carbon material (stable working voltage 0-0.8V), the porous carbon material containing sulfur at the defect sites prepared in Example 1 can increase the stable working voltage to 0-1.2V; and the CV curves at different scan rates at this potential still have excellent cycle stability. The area specific capacity calculated according to the absolute area of ​​the CV curve at a voltage scan rate of 20mV / s is 782.14mF / cm 2 .

[0060] Example 2

[0061] The preparation method of the defective porous carbon material in this embodiment is the same as that in Embodiment 1, except that the pre-formed phenolic resin film is placed in a 10wt% urea aqueous solution and ultrasonically treated for 30 minutes to finally obtain a porous carbon electrode material containing nitrogen at defect sites.

[0062] Figure 5 The GCD diagram of the three-electrode test system assembled using the porous carbon material containing nitrogen at defect sites prepared in Example 2 as the working electrode at 0-1.2V. Figure 5 It can be seen that the GCD curves at different current densities also show excellent charge and discharge characteristics. 2 The area specific capacity calculated by the discharge time at high current density is 729.17mF / cm 2 , showing excellent rate characteristics.

[0063] Example 3

[0064] The preparation method of the defective porous carbon material in this embodiment is the same as that in Embodiment 1, except that the pre-formed phenolic resin film is placed in a 1.5M ferric chloride solution and ultrasonically treated for 30 minutes to finally obtain an iron oxide composite porous carbon material.

[0065] By embedding metal manganese oxide in the macroscopic pore defects of porous carbon materials, the continuity of the electrode structure is maintained and reliable redox reactions are provided for the porous carbon electrode.

[0066] Figure 6 This is a surface SEM image of the iron oxide composite porous carbon material prepared in Example 3. Figure 6 It can be seen that the iron oxide particles are uniformly loaded on the pore walls and sheet network structure of the porous carbon material. This homogeneously distributed highly conductive active material as a heterogeneous structure provides the basis for the expansion of the stable working potential.

[0067] Figure 7 The CV graph of the three-electrode test system assembled using the iron oxide composite porous carbon material prepared in Example 3 as the working electrode at -1.2 to 0 V. Figure 7 It can be seen that the electrode maintains excellent cycle stability in the potential range of -1.2 to 0 V with different scan rates. The area specific capacity calculated based on the absolute area of ​​the CV curve at a voltage scan rate of 20 mV / s is 914.52 mF / cm 2 .

[0068] Figure 8 The GCD diagram of the three-electrode test system assembled using the iron oxide composite porous carbon material prepared in Example 3 as the working electrode at -1.2 to 0 V. Figure 8It can be seen that the GCD curves at different current densities also show excellent charge and discharge characteristics. 2 The area specific capacity calculated by the discharge time under the current density is 1734.67mF / cm 2 .

[0069] Example 4

[0070] The preparation method of the defective porous carbon material in this embodiment is the same as that in embodiment 1, except that the selected carbon precursor is a polyimide film, and finally a porous carbon electrode material containing sulfur at defect sites is obtained.

[0071] Fig. 9 This is a surface SEM image of the porous carbon material containing sulfur at defect sites prepared in Example 4. Fig. 9 It can be seen that the obvious three-dimensional porous structure provides a reliable medium for ion diffusion and transport. At the same time, the sulfur atoms in the defects of the carbon material also provide stronger electrochemical reaction activity for the electrode material and promote the transport of metal cations.

[0072] Example 5

[0073] The preparation method of the defective porous carbon material in this embodiment is the same as that in Embodiment 1, except that the laser power for pretreatment is 5.0W.

[0074] The increase in laser power during pre-carbonization increases the depth of action of the laser beam and allows for a higher pre-formed cross-sectional thickness, providing more possibilities for the subsequent construction of sulfur atom composite defect sites.

[0075] Fig.10 This is a cross-sectional SEM image of the phenolic resin film after preforming in Example 5. Fig.10 It can be seen that the phenolic resin film exhibits a uniformly distributed dense structure after pre-forming. At the same time, the results of the four-probe resistance tester show that the square resistance of the surface of the pre-treated phenolic resin film is 24.9Ω / sq, showing excellent conductive properties.

[0076] Example 6

[0077] The preparation method of the defective porous carbon material in this embodiment is the same as that in Embodiment 1, except that the carbonization treatment is a high-temperature sintering at 900°C.

[0078] Fig.11 This is a surface SEM image of the porous carbon material containing sulfur at defect sites prepared in Example 6. Fig.11 It can be seen that the defective porous carbon material prepared in Example 6 also maintains interconnected three-dimensional pore channels, providing abundant active sites for the electrochemical reaction of ions.

[0079] Comparative Example 1

[0080] The preparation method of the defective porous carbon material in this comparative example is the same as that in Example 1, except that: a low-energy CO2 laser beam is not used to pre-shape the prepared phenolic resin film.

[0081] Fig.12 The CV curve of the three-electrode test system assembled using the porous carbon material containing sulfur at defect sites prepared in Comparative Example 1 as the working electrode. Fig.12 It can be seen that the porous carbon material with sulfur at defect sites prepared by the same laser process without pre-treatment and shaping has a stable working voltage of -0.1 to 0.7 V when used as a working electrode, and polarization begins to occur when it exceeds 0.7 V. Compared with the 1.2V working potential window of the porous carbon material with sulfur at defect sites prepared by the pre-shaped phenolic resin film, the stable working voltage range of the electrode is not ideal, which proves that the pre-shaping of the precursor is the basis for realizing the extension of the working potential by utilizing the defect process of the porous carbon material.

[0082] Comparative Example 2

[0083] The preparation method of the porous carbon material in this comparative example is the same as that in Example 1, except that no sodium sulfide solution is used for defect design.

[0084] Fig.13 This is the surface element distribution diagram of the porous carbon material prepared in Comparative Example 2, and no obvious S element was observed.

[0085] Fig.14 The CV curve of the three-electrode test system assembled using the porous carbon material prepared in Comparative Example 2 as the working electrode. Fig.14 It can be seen that the peak current intensity is significantly reduced compared with Example 1, indicating that the S-compounded defect sites can produce stronger electrochemical reaction capabilities and provide higher capacitance for the composite carbon electrode material.

[0086] The above shows and describes the basic principles and main features of the present invention and the advantages of the present invention. It should be understood by those skilled in the art that the present invention is not limited to the above embodiments. The above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.

Claims

1. A method for preparing a defective porous carbon material, characterized in that: The preparation method comprises the following steps: (1) preparing a carbon precursor solution and uniformly coating the solution on a flexible substrate, and drying the solution to obtain a carbon precursor film; (2) pretreating the carbon precursor film; (3) The pretreated film is subjected to defect design and carbonization treatment to obtain a defective porous carbon material.

2. The preparation method according to claim 1, characterized in that: The carbon precursor is one or more of phenolic resin, epoxy resin, polyimide, polyamic acid, and polyether sulfone.

3. The preparation method according to claim 1, characterized in that: The coating method is one or more of a self-leveling method, a wire rod coating method, a four-sided scraper coating method, a mold coating method, and a coater coating method, and the coating thickness is 10 to 2000 μm.

4. The preparation method according to claim 1, characterized in that: The flexible substrate is one or more of PET film, copper foil, carbon-coated copper foil, copper mesh, aluminum foil, carbon-coated aluminum foil, aluminum mesh, titanium foil, stainless steel foil, nickel foil, foamed nickel, and carbon paper, and has a thickness of 5 to 200 μm.

5. The preparation method according to claim 1, characterized in that: The pretreatment is one or more of high-energy beam etching scanning, low-temperature heating treatment, and rapid flash technology treatment.

6. The preparation method according to claim 1, characterized in that: The carbonization treatment is one or more of high temperature carbonization, high energy beam etching scanning, flash Joule heat treatment, and hydrothermal reaction, and the treatment temperature is 300-3000°C.

7. The preparation method according to claim 1, characterized in that: The defect design method is one or more of the following: compounding non-metallic atoms with edge carbon atoms, removing carbon atoms on the carbon layer to form nanopores, and embedding metal oxides or hydroxides in macroscopic defects to obtain a continuous structure.

8. A defective porous carbon material prepared by the preparation method according to any one of claims 1 to 7.

9. Use of the defective porous carbon material according to claim 8 as an electrode material.

10. An asymmetric supercapacitor, characterized in that: The defective porous carbon material as claimed in claim 8 is used as the electrode material.

Citation Information

Cited By

  • High-voltage-resistant small mesoporous carbon electrode material and preparation method thereof

    CN122403419A